Postmodernisme: A very short introduction - Butler, Christopher (Oxford Oxford university press, 2003)
Postmodernism has become the buzzword of contemporary society over the last decade. But how can it be defined? In this highly readable introduction the mysteries of this most elusive of concepts are unraveled, casting a critical light upon the way we live now, from the politicizing of museum culture to the cult of the politically correct. The key postmodernist ideas are explored and challenged, as they figure in the theory, philosophy, politics, ethics and artwork of the period, and it is shown how they have interacted within a postmodernist culture.About the Series: Combining authority with wit, accessibility, and style, Very Short Introductions offer an introduction to some of life's most interesting topics. Written by experts for the newcomer, they demonstrate the finest contemporary thinking about the central problems and issues in hundreds of key topics, from philosophy to Freud, quantum theory to Islam.